2006
DOI: 10.1111/j.1365-2206.2006.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Making a home, finding a job: investigating early housing and employment outcomes for young people leaving care

Abstract: This paper presents findings from a new study of outcomes for young people leaving care funded by the Department for Education and Skills. It reports findings for a sample of 106 young people in relation to progress made in housing and employment some 12-15 months after leaving care. The generally poor employment outcomes of care leavers are acknowledged, but ingredients that make for success are also highlighted, including the value of settled care and post-care careers, sound career planning and, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 10 publications
7
105
1
7
Order By: Relevance
“…Pour d'autres, privés de ces formes de soutien de proximité, l'autre possibilité consiste à solliciter l'assistance de programmes sociaux avec le risque de voir cette période de dépendance envers les modes d'assistance publique se muer en problématique d'exclusion. En l'absence de soutien facilitant la négociation du PVA, la transition a plutôt tendance à s'accélérer (Wade & Dixon, 2006) et à se traduire par l'endossement prématuré de responsabilités adultes.…”
Section: Problématique De Rechercheunclassified
“…Pour d'autres, privés de ces formes de soutien de proximité, l'autre possibilité consiste à solliciter l'assistance de programmes sociaux avec le risque de voir cette période de dépendance envers les modes d'assistance publique se muer en problématique d'exclusion. En l'absence de soutien facilitant la négociation du PVA, la transition a plutôt tendance à s'accélérer (Wade & Dixon, 2006) et à se traduire par l'endossement prématuré de responsabilités adultes.…”
Section: Problématique De Rechercheunclassified
“…Berzin et al [34] reported that stable housing became a critical goal for young people leaving foster care, referring to it as the most salient prerequisite for independent living. Wade & Dickson [19] found secure independent housing to be the factor youth most highly associated with mental well-being, overriding the significance of both education and employment. Viewed from this perspective, adequate and secure housing holds top priority on leveling the road to independent adult living.…”
Section: Facilitating Independent Livingmentioning
confidence: 99%
“…The significance of "normality", with privacy and a place to house belongings is emphasized in several studies [19] [24] [34]. According to Padgett [24], having one's own home contributes to ontological security through a contribution to the sense of continuity regarding life events.…”
Section: Facilitating Independent Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest scores were reported among children in a day-group setting, followed by children in secure placements, while children from mainstream schools came third (comparison group), and the worst results were found among the young people in the residential group. The quality of life in residential care leavers may be affected by objective difficulties relating to living conditions in areas such as accommodations (Biehal & Wade, 1999, Wade & Dixon, 2006, employment, education (Jackson, 2008), income, and health (Dixon, 2008); as well as by subjective satisfaction with life -self-respect, mental health, partner relations, social support, desires, expectations, and meaning of life (Dixon, 2008).…”
mentioning
confidence: 99%